Pastoral Inclusive for the Disabled in Amoris Laetitia Perspective and Implementation in the Church - Angela Florida Mau (International Journal of Christian Education and Philosophical Inquiry, 2024)
Disability refers to the limited roles experienced by people with disabilities. In most groups of society, the existence of disabled people is often viewed negatively. Based on the concept of normality, this group of people tends to give a negative stigma to people with disabilities as abnormal or abnormal humans. What people with disabilities experience is considered a curse, a hereditary disease, or even the result of sinful actions. The Catholic Church in its various teachings places disabled people as God's ideal creatures who are equal to other humans. Specifically, in his apostolic exhortation Amoris Latetitia, Pope Francis invites families and Christian communities to accept and respect the rights of people with disabilities. The presence of disabled people should be seen as a gift from God, and the acceptance of families and Christian communities is the work of the Holy Spirit and a testimony of the gift of human life. This research is a descriptive qualitative study which aims to understand and find concrete implementation of the Catholic Church's view of people with disabilities from the perspective of Amoris Laetitia. The research results show that the Catholic church's views in Amoris Laetitia can be the basis for inclusive pastoral care to open up, embrace and involve people with disabilities in all aspects of church life. Forms of inclusive pastoral care that can be carried out include providing education and awareness about disabled people for the church community, providing accessible facilities for disabled people, providing pastoral and spiritual support, and actively involving disabled people in liturgical and other church activities.